High conductive aluminium metal matrix composites with carbon inserts obtained by casting processes. (2019) - Todaro, Ivan; Squatrito, Rosario; Essel, Shai; Zeidler, Henning
Abstract: This work focuses on the production of high conductive Aluminum based MMC or co-cast components obtained by casting processes. The activity started from the "reinforcement" materials to be used for the MMC fabrication. Carbon based materials were chosen and their characterization under the thermal point of view was carried out. Several arrangements for matrix-reinforcement and matrix-insert couples were evaluated and their potential performances were estimated via numerical simulation. Aluminum-Diamond, Aluminum-Reduced Graphene Oxide and Aluminum-Thermal Pyrolytic Graphite components were produced and their performances were experimentally evaluated. Finally, demonstrator utilizing the novel materials were produced and tested in their relevant working condition.